Herbivore‐induced branching increases sapling survival in temperate forest canopy gaps. (7th April 2022) - Churski, Marcin; Charles‐Dominique, Tristan; Bubnicki, Jakub W.; Jędrzejewska, Bogumiła; Kuijper, Dries P. J.; Cromsigt, Joris P. G. M.
Abstract: Tree architectures reflect the main abiotic and biotic selection pressures determining tree growth and survival. Studies have shown that trees growing in herbivore‐dominated ecosystems, such as savannas, develop denser, more divaricate 'cage'‐like architectures in response to chronic browsing pressure (also known as 'brown world' architectures). In contrast, trees growing under resource‐limited conditions develop traits that allow them to better compete for abiotic resources (referred to as 'green world' architectures); for example, light limitation can induce trees to form more pole‐like structures that allow them to grow faster in height. In temperate forests, abiotic drivers have traditionally been assumed to be the main factors affecting plant architecture. However, gap dynamics typically characterize old‐growth temperate forests, where disturbances such as storms create gaps with temporary high‐light availability, but also attracting intense mammalian browsing. Under such conditions, one would expect tree saplings to exhibit high architectural plasticity enabling them to develop a 'cage' in response to high herbivore pressure, but when herbivore pressure declines switch to a more pole‐like structure that allows them to grow quickly in height and compete for light. We tested the ability of five dominant European tree species to induce a 'cage' architecture (hereafter referred to as 'cage plasticity') under contrasting light and herbivory regimes in a full‐factorial experiment in Białowieża Forest. We planted 720 young tree saplings in six replicated blocks in which we manipulated ungulate browsing (exclosure vs. control) and light levels (gap vs. closed forest). Two out of the five species (hornbeam Carpinus betulus and lime Tilia cordata ) were able to develop a cage when exposed to ungulate herbivores but only under high‐light conditions. These two species had the highest survival rates in the herbivory treatment over a 10‐year period. Synthesis . Cage plasticity in temperate forest tree species may reflect an overlooked adaptation to mammal herbivory originating in a past when large mammals exerted strong selection pressures in European ecosystems. Our findings challenge the view of closed‐canopy forest communities being solely driven by abiotic drivers and call for a re‐evaluation of the importance of large herbivores in shaping the functional traits of temperate tree species. Abstract : Cage plasticity in temperate forest tree species may reflect an overlooked adaptation to mammal herbivory originating in a past when large mammals exerted strong selection pressures in European ecosystems. Our findings challenge the view of closed‐canopy forest communities being solely driven by abiotic drivers and call for a re‐evaluation of the importance of large herbivores in shaping the functional traits of temperate tree species. Podsumowanie: Pokrój drzew odzwierciedla główne presje selekcyjne determinujące ich wzrost i przeżywalność. Dotychczasowe badania wykazały, że w ekosystemach zdominowanych przez roślinożerców, takich jak sawanny, drzewa wykształcają gęstszą, bardziej rozgałęzioną strukturę pędów przypominającą krzew lub „klatkę" (ang. „cage"). Jest to reakcja na długotrwałą presję zgryzania. Z kolei w środowiskach ograniczanych przez zasoby, drzewa rozwijają cechy, które pozwalają im lepiej konkurować o zasoby abiotyczne, na przykład ograniczony dostęp do światła sprawia, że drzewa przyjmują pokrój bardziej wydłużony i mniej rozgałęziony (ang. „pole"), który odzwierciedla wzrost na wysokość. W lasach strefy umiarkowanej tradycyjnie przyjmuje się, że klimat i zasoby (np. dostępność światła) są głównymi czynnikami wpływającymi na pokrój drzew. Należy jednak wspomnieć o lukach w drzewostanie, gdzie panują odmienne warunki i działają inne czynniki selekcyjne. Powstałe na skutek zaburzeń luki charakteryzują się wysoką dostępnością światła, a także przyciągają intensywne żerowanie ssaków kopytnych. W takich warunkach można oczekiwać, że siewki drzew będą wykazywały dużą plastyczność pokroju, i w odpowiedzi na presję roślinożerców stworzą pokrój klatkowy. Gdy presja roślinożerców zmaleje, zmienią pokrój na bardziej wydłużony, co pozwoli im na szybki wzrost na wysokość i konkurowanie o światło. W eksperymencie przeprowadzonym w Puszczy Białowieskiej badaliśmy zdolność pięciu dominujących europejskich gatunków drzew do wykształcania pokroju klatkowego (zwanej dalej "plastycznością pokroju klatkowego"). Mierzyliśmy wpływ różnego reżimu świetlnego i presji ssaków kopytnych. Posadziliśmy 720 młodych sadzonek drzew w sześciu powtarzających się blokach, w których manipulowaliśmy intensywnością zgryzania (zagroda vs. kontrola) i poziomem światła (luka vs. zwarty las). Dwa z pięciu gatunków (grab Carpinus betulus i lipa Tilia cordata ) były w stanie rozwinąć pokrój klatkowy, gdy były zgryzane przez roślinożerców, ale tylko wtedy, gdy miały dostęp do światła. Oba gatunki miały najwyższe wskaźniki przeżywalności w warunkach zgryzania w okresie 10 lat. Synteza . Plastyczność pokroju klatkowego u gatunków drzew lasów umiarkowanych może odzwierciedlać przeoczoną adaptację do zgryzania przez ssaki roślinożerne. Adaptacja ta może pochodzić z przeszłości, z czasów kiedy duże ssaki wywierały silną presję selekcyjną w ekosystemach europejskich. Nasze wyniki podważają pogląd, że zbiorowiska leśne są kształtowane wyłącznie przez zasoby. Badając ekosystemy leśne powinniśmy zacząć zwracać większą uwagę na znaczenie dużych roślinożerców w kształtowaniu cech funkcjonalnych gatunków drzew klimatu umiarkowanego.